Monitoring KAT6A-CREBBP measurable residual disease in t(8;16) therapy-related acute myeloid leukemia. (May 2022) - Bhreathnach, Úna; Doherty, Dearbhla; Murphy, Karen; Flynn, Catherine M.; Langabeer, Stephen E.
Highlights: Therapy-related AML with the t(8;16) is uncommon and associated with a poor prognosis. Hematopoietic allogeneic stem cell transplantation remains the only curative option. KAT6A-CREBBP transcript identification is necessary for measurable residual disease. RT-qPCR monitoring confirms the efficacy of allogeneic stem cell transplantation. In t(8;16) AML, measurable residual disease peri-transplant may influence prognosis.